Formation of digital competence in the scientific research of a master student in professional education in the field of physical education and sports - Shchuchka T.A.; Gnezdilova N.A.; Gerasimova E.N. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify and theoretically justify the use of methodological approaches in solving the problem of developing digital competence in the scientific research of a master's student in vocational education and management in the field of physical culture and sports. Methods and structure of the study. An analysis of the scientific literature related to the research topic was carried out [1, 3, 4, 5]. Results and conclusions. In solving the problem of developing digital competence in a scientific study of a master's student in vocational education and management in the field of physical culture and sports, the use of such methodological approaches as problem-oriented and active learning, competency-based, systemic, personality-oriented, integrative, and activity-based is proposed. It is noted that the methodological approaches under consideration make it possible to expand the content of the research activities of a master's student in the field of vocational education and management in the field of physical culture and sports, which helps to increase his independent creative activity; development of skills in searching and analyzing a large amount of information, the ability to apply various methods of objective assessment of one’s work, as well as the formation of other professional competencies and personal qualities that meet the current needs of modern practice.